Impacts of an ethanol‐blended fuel release on groundwater and fate of produced methane: Simulation of field observations. Issue 8 (7th August 2013) - Rasa, Ehsan; Bekins, Barbara A.; Mackay, Douglas M.; de Sieyes, Nicholas R.; Wilson, John T.; Feris, Kevin P.; Wood, Isaac A.; Scow, Kate M.
Abstract : [1] In a field experiment at Vandenberg Air Force Base (VAFB) designed to mimic the impact of a small‐volume release of E10 (10% ethanol and 90% conventional gasoline), two plumes were created by injecting extracted groundwater spiked with benzene, toluene, and o ‐xylene, abbreviated BT o X (no‐ethanol lane) and BT o X plus ethanol (with‐ethanol lane) for 283 days. We developed a reactive transport model to understand processes controlling the fate of ethanol and BT o X. The model was calibrated to the extensive field data set and accounted for concentrations of sulfate, iron, acetate, and methane along with iron‐reducing bacteria, sulfate‐reducing bacteria, fermentative bacteria, and methanogenic archaea. The benzene plume was about 4.5 times longer in the with‐ethanol lane than in the no‐ethanol lane. Matching this different behavior in the two lanes required inhibiting benzene degradation in the presence of ethanol. Inclusion of iron reduction with negligible growth of iron reducers was required to reproduce the observed constant degradation rate of benzene. Modeling suggested that vertical dispersion and diffusion of sulfate from an adjacent aquitard were important sources of sulfate in the aquifer. Matching of methane data required incorporating initial fermentation of ethanol to acetate, methane loss by outgassing, and methane oxidation coupled to sulfate and iron reduction. Simulation of microbial growth using dual Monod kinetics, and including inhibition by more favorable electron acceptors, generally resulted in reasonable yields for microbial growth of 0.01–0.05. Key Points: Reactive transport model of anaerobic ethanol and BToX field experiment Microbial growth simulations of sulfate reducers, fermenters and methanogens Simulations suggest methane oxidation is coupled to sulfate and iron reduction